AN ANALYSIS OF DIRECTIVE ILLOCUTIONARY ACTS OF ELEANOR FALCO IN ‘TO CATCH A KILLER’ MOVIE BY DAMIÁN SZIFRÓN - Monangin, Christa; Andries, Fivy A.; Rorimpandey, Rinny S. (Program Studi Pendidikan Bahasa Inggris, 2024)
This research aims to find out the types of directive illocutionary acts and explain how perfomerd Eleanor Falco in